Dermoscopic monitoring of efficacy of ingenol mebutate in the treatment of pigmented and non‐pigmented basal cell carcinomas. Issue 1 (12th November 2016) - Diluvio, Laura; Bavetta, Mauro; Di Prete, Monia; Orlandi, Augusto; Bianchi, Luca; Campione, Elena
Abstract: Basal cell carcinoma is the most common non‐melanoma skin cancer, and its incidence continues to raise. Although surgery can be considered the mainstay of therapy, new current pharmacological options are available and focus on tumor eradication, maximizing cosmetic results, and functional capacity. Several studies have recently reported on safety and efficacy of topical ingenol mebutate gel, a derivative of the plant Euphorbia Peplus, used to treat actinic keratosis and superficial basal cell carcinoma. In our knowledge, we report for the first time the dermoscopic evaluation of outcome and monitoring of superficial pigmented and non‐pigmented basal cell carcinomas in four patients treated by this novel non‐ablative agent. Ingenol mebutate gel therapy has showed to be effective and without important side‐effects for pigmented and non‐pigmented superficial basal cell carcinomas. We emphasize the usefulness of dermoscopy in supporting the clinical diagnosis and excluding the presence of tumor residue or recurrence. In a future scenario, we hope it will be soon possible to follow‐up the lesions, after treatment, avoiding post‐control biopsy punch.